Pemberdayaan Guru Madrasah Diniyah Al-Falah Asemjajar Melalui Pelatihan Bahasa Inggris Dasar Sebagai Upaya Adaptasi Terhadap Globalisasi - Mita Asmira (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
Educational globalization requires teachers to possess global competencies, including basic English proficiency as a means of accessing information and enhancing professional development. However, teachers in Madrasah Diniyah as non-formal religious educational institutions often face limitations in mastering basic English skills. This community service program aimed to improve basic English competence and professional awareness of teachers at Madrasah Diniyah Al-Falah Asemjajar in responding to the challenges of educational globalization. The program employed observation, training, and evaluation stages. The training was conducted through interactive lectures, discussions, pronunciation practice, and simple conversation simulations tailored to the teachers’ instructional context. The results indicate an improvement in teachers’ basic English skills, particularly vocabulary, pronunciation, and the use of simple expressions, as well as positive changes in attitudes, including increased confidence and learning motivation. Furthermore, the program enhanced teachers’ awareness of the importance of English as a supporting competence for professionalism and access to global learning resources. This activity contributes to empowering Madrasah Diniyah teachers to adapt to global educational developments while maintaining religious values.